Arab American women : representation and refusal - Suleiman, Michael W.; Joseph, Suad; Cainkar, Louise (Critical Arab American studies., 2021)
"This rigorous, multidisciplinary volume on Arab American women includes contributions from scholars and activists in in a diverse array of fields, including history, sociology, anthropology, literary studies, media studies, women and gender studies, and creative writing"--